PARADIGMA JILBAB DULU DAN SEKARANG - Ahmad Badwi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2015)
The term of “jilbab” means loose of clother which is able to cover a woman’s part of bodies which may not be visibe while perfoming a ritual except face and two palms a hands, so circle that can be seen. Etimologically, jilbab is a masdar (gerund) formed from verb “jalaba” which means ‘to bring” bring” or “to collect”. Its plural form is “jalabin”. It menas auter garment, mantle, and cloack that can cover all wamen’s bodies. Jilbab means also, specially when the Qur’an revealed, is a clother that covers bodies from up to down, a long cover of head, covering blanket, the second layer. Jilbab of course, for women has a main purpose to cover women’s part of bodies, in order to be safe from an interaction and a relation between a man and a woman from illegal relation according to view of view of Islamic law. Jilbab has also purposes to show a woman’s simplicity and core personal values, and to protect herself from many possinilities in a life that related to unhoped thing.